Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.

Solve for y.



7y - 6y - 10 = 13

y = -23
y = -3
y = 3
y = 23


Sagot :

Answer:

23

Step-by-step explanation:

7y -6y -10 = 13

y - 10 = 13

y = 13 +10

y= 23